Economic Constraints – the Growing Challenge for Western Breast Cancer Centers - Seidel, Rene P. (S. Karger GmbH, 2013)
Breast cancer care in Western countries has reached a considerable level of quality and standardization, which has contributed to the decline in breast cancer mortality. Certified Breast Cancer Centers (BCC) represent an important element of this development. Related to changes in reimbursement and growing costs, BCC face economic constraints which ultimately could endanger the achievements of the past. Thus, BCC have to optimize their care strategies from an economic perspective, particularly by increasing efficiency but also by adapting their service portfolio. This could result in competitive advantages and additional revenue by increasing case numbers and extra charges to patients. Furthermore, an intensification of collaboration with the outpatient sector resulting in an integrated and managed ‘trans-sectoral’ care approach which could allow to shift unprofitable procedures to the outpatient sector – in the sense of a win-win situation for both sectors and without loss of care quality – seems reasonable. Structured and specialized consulting approaches can further be a lever to fulfill economic requirements in order to avoid cuts in medical care quality for the sake of a balanced budget. In this review, economic constraints of BCC with a focus on the German healthcare system and potential approaches to ameliorate these financial burdens are being discussed.